Subject and Use Index (Bulletin of the Center for Children's Books, 2020)
In the case of subject headings, the subhead "stories" refers to books for the readaloud audience; "fiction," to those books intended for independent reading. Jackson; Jocelyn; Soman Dinosaurs–stories: Nye Disasters–fiction: Blankman Dogs–fiction: Finnegan Ducks–stories: Jarvis Dystopias–fiction: Staniszewski Ecology: Soltis; Winter, Jeanette; Winter, Jonah Economics: Svetcov Environmental studies: Engle; Hopkins; Nye Poland–fiction: Cameron Politics: Blumenthal Politics–fiction: Bartlett Poverty–fiction: Padian Rabbits–stories: Scheuer Reading aloud: